Implementasi Manajemen dan Kepemimpinan Islami dalam Meningkatkan Kinerja Organisasional - Syaipullah Ahmad; Khoirun Rambe; Nurul Sakinah; Khadijah Khadijah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic management and leadership have an important role in improving organizational performance. This study aims to analyze the implementation of Islamic management and leadership in improving organizational performance. This research uses quantitative methods with information collection techniques through questionnaires. The results showed that the implementation of Islamic management and leadership has a positive impact on organizational performance.